2010
DOI: 10.1037/a0019086
|View full text |Cite
|
Sign up to set email alerts
|

Rally effects, threat, and attitude change: An integrative approach to understanding the role of emotion.

Abstract: Rally 'round the flag effects (J. E. Mueller, 1970) represent sudden and dramatically powerful situation-specific shifts in attitudes toward the American president. However, the extant literature has yet to fully clarify the nature of the psychological dynamics associated with this effect. These ambiguities reflect fundamental differences of opinion among scholars on some very basic questions such as whether overtly experienced emotion should mediate these attitudinal shifts or whether these changes reflect mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 57 publications
5
105
1
1
Order By: Relevance
“…The Bush administration's efforts sought to invoke and channel the affective salience of 9/11 and play up ongoing fears; they also worked to appeal to and redirect lingering moral 124. Lambert et al 2010. 125.…”
Section: Affective Strategiesmentioning
confidence: 95%
“…The Bush administration's efforts sought to invoke and channel the affective salience of 9/11 and play up ongoing fears; they also worked to appeal to and redirect lingering moral 124. Lambert et al 2010. 125.…”
Section: Affective Strategiesmentioning
confidence: 95%
“…Anger and power are closely linked to approach motivation (Carver & Harmon-Jones, 2009;Keltner et al, 2003), and so ideologies that wield them should be more able to activate approach motivation. Indeed, moral outrage and worldview defensive reactions to threats are often mediated by anger (Lambert et al, 2010;Mullen & Skitka, 2006). In sum, although one can be reactively extreme for either liberal or conservative ideals, conservatism may be more appealing and conducive to sustaining approach motivation because it is more idealistic, consistent, and comfortable exercising power and aggression.…”
Section: Conservative Idealsmentioning
confidence: 98%
“…As far as existential fear is concerned, a line of research suggests that death anxiety tends to be associated with political conservatism, right-wing authoritarianism and system justifying beliefs (Wilson, 1973; Jost et al, 2003, 2007; Hennes et al, 2012). Experimental studies also showed that manipulations of mortality salience (e.g., Landau et al, 2004; Cohen et al, 2005; Nail et al, 2009) and terrorism salience (Ullrich and Cohrs, 2007) tend to shift people's political opinions and preferences toward conservatism (but see also Kosloff et al, 2010; Lambert et al, 2010 for different results). Besides fear, disgust is also associated to political ideology.…”
Section: Introductionmentioning
confidence: 99%